Prices for Crop and Livestock Cost-Return Budgets - Dhuyvetter, Kevin C.; Kastens, Terry L.; Dumler, Troy J.; Tonsor, Glynn T. (My University, 2010)
A publication detailing wheat, corn, grain sorghum, and soybean price projections.
MF1013_2010-11
Keywords: MF1013; Economics; Crops; MF